Hierarchical Organization of Segmentation in Non-Functional Action Sequences - Nielbo, Kristoffer Laigaard (Journal for the cognitive science of religion, 2013)
Both folk and scientific taxonomies of behavior distinguish between instrumental and ritual behavior. Recent studies indicate that behaviors dominated by ritual features tend to increase cognitive load by focusing attentional and working memory resources on low-level perceptual details and psycho-physics. In contrast to the general consensus on anthropology and the study of religion, one study did not find any modulation effect of expectations (e.g., cultural information or priors) on cognitive load. It has, therefore, been suggested that the increase reflects a perceptual mechanism that drives categorization of ritual behavior. The present study investigated how an increase in cognitive load elicited by ritual behavior can influence hierarchically-related representations of actions and if expectation can modulate such hierarchical action representations. The study found that hierarchical alignment during segmentation of actions with ritual features was reduced in comparison to instrumental actions but that expectations only vaguely modulate this reduction. It is argued that these results lend support to the resource depletion model ritual behavior.